2016
DOI: 10.1016/j.cell.2015.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of the Biogenesis Factor Rei1 Probes the Ribosomal Tunnel during 60S Maturation

Abstract: Eukaryotic ribosome biogenesis depends on several hundred assembly factors to produce functional 40S and 60S ribosomal subunits. The final phase of 60S subunit biogenesis is cytoplasmic maturation, which includes the proofreading of functional centers of the 60S subunit and the release of several ribosome biogenesis factors. We report the cryo-electron microscopy (cryo-EM) structure of the yeast 60S subunit in complex with the biogenesis factors Rei1, Arx1, and Alb1 at 3.4 Å resolution. In addition to the netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
160
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(171 citation statements)
references
References 55 publications
(128 reference statements)
9
160
1
1
Order By: Relevance
“…Subsequently, Arx1 is dissociated by Jjj1 and Rei1 [103]. Interestingly, as shown by high-resolution cryo-EM, Rei1 and the closely related Reh1 probe the exit tunnel in a manner similar to Nog1 [25,28,30]. During P-stalk assembly, recruitment of uL10 is coupled with the release of Yvh1, which has previously displaced Mrt4 from pre-60S particles [103,104].…”
Section: Assembly Of the Lsumentioning
confidence: 95%
See 1 more Smart Citation
“…Subsequently, Arx1 is dissociated by Jjj1 and Rei1 [103]. Interestingly, as shown by high-resolution cryo-EM, Rei1 and the closely related Reh1 probe the exit tunnel in a manner similar to Nog1 [25,28,30]. During P-stalk assembly, recruitment of uL10 is coupled with the release of Yvh1, which has previously displaced Mrt4 from pre-60S particles [103,104].…”
Section: Assembly Of the Lsumentioning
confidence: 95%
“…A few of these preribosomal particles were visualized at relatively low resolution by EM [21][22][23][24]. Recent progress in cryo-EM has enabled a quantum jump by permitting the visualization of preribosomal particles at atomic or near-atomic resolution [25][26][27][28][29][30][31][32][33]. These studies not only provided a detailed view of the overall architecture of Glossary Biogenesis factors: the efficient and accurate assembly of ribosomal subunits is promoted by more than 200 proteins that are transiently associated with preribosomal particles; these proteins are collectively referred to as biogenesis factors, or alternatively as transacting or assembly factors.…”
Section: Trendsmentioning
confidence: 99%
“…A central cavity in the fold of Arx1, which corresponds to the catalytic pocket of homologous MAP enzymes, has been suggested to serve as a binding site for FG-repeat nucleoporins of the NPC, thereby mediating nuclear export ). However, the structures of the natively purified Arx1 particle Leidig et al 2014), as well as the higher-resolution structures of in vitro reconstituted complexes of the yeast 60S subunit and Arx1 (Greber et al 2012(Greber et al , 2016, showed that this pocket faces the ribosomal subunit surface near the polypeptide tunnel exit, and that access to it is restricted by several Arx1-specific extensions to the conserved MAPlike core fold that are involved in interactions with the 60S subunit ( Fig. 7A; Greber et al 2016).…”
Section: Maturation Of the Central Protuberance And Checkpoint Contromentioning
confidence: 99%
“…However, the structures of the natively purified Arx1 particle Leidig et al 2014), as well as the higher-resolution structures of in vitro reconstituted complexes of the yeast 60S subunit and Arx1 (Greber et al 2012(Greber et al , 2016, showed that this pocket faces the ribosomal subunit surface near the polypeptide tunnel exit, and that access to it is restricted by several Arx1-specific extensions to the conserved MAPlike core fold that are involved in interactions with the 60S subunit ( Fig. 7A; Greber et al 2016). Even though these observations do not exclude that highly flexible FG-repeats of nucleoporins can access the Arx1 cavity, it is possible that structural elements of Arx1 other than the putative nucleoporin-binding pocket are involved in mediating nuclear export.…”
Section: Maturation Of the Central Protuberance And Checkpoint Contromentioning
confidence: 99%
See 1 more Smart Citation